2001
DOI: 10.1046/j.0960-7692.2001.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal intracranial hemorrhage: is minor maternal trauma a possible pathogenetic factor?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 31 publications
1
48
1
1
Order By: Relevance
“…After that age, the subependymal germinal matrix undergoes a progressive process of involution, which increases the vulnerability of its tenuous capillary network [4]. In our series, all fetuses were diagnosed as having ventriculomegaly by obstetric US at 31–36 weeks of gestation and no abnormal findings were detected by routine US until 27–33 weeks.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…After that age, the subependymal germinal matrix undergoes a progressive process of involution, which increases the vulnerability of its tenuous capillary network [4]. In our series, all fetuses were diagnosed as having ventriculomegaly by obstetric US at 31–36 weeks of gestation and no abnormal findings were detected by routine US until 27–33 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…In our case 1 of twins, only the one of the twins developed GMIVH, suggesting that systemic disorders such as maternal coagulopathies are not considered a significant factor, although fetal ‘focal’ coagulopathy could not be ruled out. Strigini et al [4] reported 5 cases of GMIVH, with the similarity of histories involving minor maternal physical trauma in all cases, and they concluded that trauma is at least a contributing factor to the pathogenesis of fetal GMIVH. In our 5 cases, no apparent etiology including maternal trauma could be identified, and the fetuses were appropriate for their gestational age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causative role of maternal accidents was extremely likely in one patient, and probable but "unproved" in the remaining cases. Another more cogent example is from Strigini et al 15 In five consecutive cases of fetal intracranial hemorrhage, the similarity of histories involving minor maternal physical trauma (three motor vehicle related and two falls), together with the absence of any known factor predisposing to fetal intracranial hemorrhage, suggested that minor trauma was at least a contributing factor to the observed pathology. Other similar but smaller case series or reports have been reported 16 raising the issue of trauma as a true teratogen (defined by the US Environmental Protection Agency as "The introduction of nonhereditary birth defects in a developing fetus by exogenous factors such as physical or chemical agents acting in the womb to interfere with normal embryonic development").…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic measures include maternal dietary modification 1 , repeat thoracocentesis 2 , thoracoamniotic shunting 3 , intrapleural injection of maternal blood 4 and pleurodesis with OK-432 5 -9 . We read with interest the articles (two published in 2001 5,6 and one in 2003 7 ) in this journal on pleurodesis using OK-432. The first two cases of our own experience with OK-432 as a therapeutic agent for hydrops fetalis (in one of which it was used for pleurodesis) were published elsewhere 9 .…”
Section: Fetal Ok-432 Pleurodesis: Complete or Incomplete?mentioning
confidence: 99%